2002
DOI: 10.1161/01.atv.0000022850.59845.e0
|View full text |Cite
|
Sign up to set email alerts
|

Value of HDL Cholesterol, Apolipoprotein A-I, Lipoprotein A-I, and Lipoprotein A-I/A-II in Prediction of Coronary Heart Disease

Abstract: on behalf of the PRIME Study Group* Objective-We have examined the association between the incidence of coronary heart disease (CHD) and plasma high density lipoprotein (HDL) cholesterol, apolipoprotein A-I (apoA-I), and 2 HDL fractions, lipoprotein A-I and lipoprotein A-I:A-II. Methods and Results-These parameters were measured in subjects recruited in France and in Northern Ireland in the Prospective Epidemiological Study of Myocardial Infarction (PRIME) Study, a prospective cohort study. Among the subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
101
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 33 publications
5
101
0
3
Order By: Relevance
“…Hypertriglyceridemic waist and CVD risk in men S Czernichow et al Infarction (PRIME). 29 More recently, in the INTERHEART Study, a case-control study based on more than 29 000 subjects from 52 countries, apo-B/A1 ratio was associated with a 3.87-fold (3.39-4.42) increased risk of acute myocardial infarction after adjustment for age, sex and smoking. 21 Similar results were observed in the prospective AMORIS Study, with fatal myocardial infarction as outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemic waist and CVD risk in men S Czernichow et al Infarction (PRIME). 29 More recently, in the INTERHEART Study, a case-control study based on more than 29 000 subjects from 52 countries, apo-B/A1 ratio was associated with a 3.87-fold (3.39-4.42) increased risk of acute myocardial infarction after adjustment for age, sex and smoking. 21 Similar results were observed in the prospective AMORIS Study, with fatal myocardial infarction as outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Total cholesterol (TC) and triglyceride (TG) analyses were carried out with enzymatic methods using the cholesterol enzymatique color II reactive and triglycerides enzymatique trinder II reactive (Biotrol, Paris). High-density lipoproteins (HDL-C) quanti cation was performed with CHOLHDL (Mg-dextran sulfate) reactive (Sclavo, Sovicille, Italy) via enzymatic measurement of the remaining cholesterol in the supernatant following precipitation of very-low-density lipoprotein (VLDL) and LDL-C. e Friedewald formula was used to determine VLDL and LDL-C values: [10]. Blood samples obtained for serum Lp(a) measurement were separated from the serum by centrifugation for 30 min, and then were stored in a deep freezer at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have clearly shown a correlation between lipoprotein lipid fractions and CAD [7][8][9][10]. e results of two studies on the relationship between Lp(a) levels and CAD report con icting information [7,8].…”
mentioning
confidence: 99%
“…Coronary heart disease (CHD) 2 is one of the prime causes of an increase in the mortality rate worldwide. Over the past few years, various epidemiological studies have provided ample evidence that increased levels of HDL, by transporting cholesterol from atherosclerotic plaques to liver for excretion, can arrest the progression of CHD (1,2).…”
mentioning
confidence: 99%
“…Over the past few years, various epidemiological studies have provided ample evidence that increased levels of HDL, by transporting cholesterol from atherosclerotic plaques to liver for excretion, can arrest the progression of CHD (1,2). Subsequent preclinical studies on overexpression of apolipoprotein A-I (apoA-I), the major protein constituent of HDL, have reported significant reduction in CHD risk (3,4).…”
mentioning
confidence: 99%